The effect of reactivity on the carbonation of MgO cements - Teo, Sean Zhe Wei (2016)
The sustainable appeal of Calcined dolomite produces CaCO3, CaO, and MgO depending on the calcination temperature of the dolomite. This study aims to explore the effects of different calcination temperatures to produce reactive MgO as a cement binder. Dolomite was calcined at 800oC (D800) and 900oC (D900) and use as a full or partial replacement of MgO and the effects were investigated using compressive tests, powder X-ray diffraction (XRD), scanning electron microscope (SEM). D800 concrete outperformed the control Mgo and D900 by 24% and 218% respectively, with a 28-day strength of 26.36MPa.The presence of dense formation of carbonation products in D800 were observed by SEM,XRD, and TGA. Remove